Method for producing boron-containing transition metal carbonate and method for producing positive electrode active material

A method for producing boron-containing transition metal carbonates through controlled aqueous solution reactions and firing processes addresses the inefficiencies of high-temperature boron introduction, resulting in improved lithium ion battery capacity and reduced gas generation.

JP2024179909AActive Publication Date: 2024-12-26PRIME PLANET ENERGY & SOLUTIONS INC
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
JP2023099238
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2023-06-16
Publication Date
2024-12-26
Estimated Expiration
2043-06-16

AI Technical Summary

Technical Problem

Introducing boron into lithium-transition metal composite oxides through high-temperature heat treatment reduces productivity and increases energy consumption, while coprecipitation methods result in insufficient boron introduction, limiting the effectiveness of improving lithium ion secondary battery characteristics.

Method used

A method involving the preparation of an initial aqueous solution with specific pH ranges and controlled oxygen concentration, followed by a crystallization reaction using ammonium and borate ion donors, and subsequent mixing and firing of transition metal carbonates to produce boron-containing lithium transition metal composite oxides without high-temperature heat treatment.

Benefits of technology

This method enhances the capacity and reduces gas generation during storage in lithium ion secondary batteries by efficiently introducing boron into the positive electrode active material, demonstrating high capacity and gas suppression effects.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2024179909000001_ABST
    Figure 2024179909000001_ABST
Patent Text Reader

Abstract

To provide a method for producing a precursor for a positive electrode active material that does not require heat treatment at a high temperature for introducing boron and that, when used as a positive electrode active material, is highly effective in increasing the capacity of lithium-ion secondary batteries and suppressing gas generation during storage.SOLUTION: A method for producing a boron-containing transition metal carbonate includes: a step of preparing an initial aqueous solution containing an ammonium ion donor and a borate ion donor in a reaction tank; and a step of forming a reaction solution to perform recrystallization by adding to the initial aqueous solution a raw aqueous solution containing transition metals, a boron-source aqueous solution containing an ammonium donor and a borate ion donor, and a pH adjustment solution. The pH of the initial aqueous solution (25°C) is 5.5-7.0. The oxygen concentration in the reaction tank is equal to or less than 5 vol%. The transition metals include Ni. The pH of the boron-source aqueous solution (25°C) is 7.5 to 9.5. The pH adjustment solution contains carbonate. The pH of the reaction solution (25°C) is 5.5-7.0.SELECTED DRAWING: Figure 1
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a method for producing a boron-containing transition metal carbonate. The present invention also relates to a method for producing a positive electrode active material using the boron-containing transition metal carbonate. [Background technology]

[0002] 2. Description of the Related Art In recent years, secondary batteries such as lithium-ion secondary batteries have been suitably used as portable power sources for personal computers, mobile terminals, and the like, and as power sources for driving vehicles such as electric vehicles (BEVs), hybrid electric vehicles (HEVs), and plug-in hybrid electric vehicles (PHEVs), among others.

[0003] Lithium transition metal composite oxides such as lithium nickel cobalt manganese composite oxides are known as positive electrode active materials for lithium ion secondary batteries. A technique for introducing boron (B) into lithium transition metal composite oxides is known (see, for example, Patent Documents 1 to 3). Patent Document 1 describes that the introduction of boron can increase the capacity of a lithium ion secondary battery. Patent Document 2 describes that the introduction of boron can suppress gas generation during storage of a lithium ion secondary battery. In Patent Documents 1 and 2, boron is introduced into the positive electrode active material by mixing a lithium transition metal composite oxide with a boron source and heat-treating the mixture at a high temperature (specifically, several hundred degrees Celsius). In Patent Document 3, boron is introduced into a hydroxide of a precursor of a positive electrode active material prepared by a coprecipitation method. [Prior art documents] [Patent documents]

[0004] [Patent Document 1] JP 2009-146739 A [Patent Document 2] JP 2010-40382 A [Patent Document 3] JP 2023-8932 A Summary of the Invention [Problem to be solved by the invention]

[0005] However, the introduction of boron into lithium transition metal composite oxides by high-temperature heat treatment leads to a decrease in productivity. In addition, high-temperature heat treatment consumes a lot of energy, leading to an increase in carbon dioxide emissions. On the other hand, when boron is introduced into a precursor hydroxide by coprecipitation, almost no boron is introduced, making it difficult to obtain a significant effect of improving the performance of lithium-ion secondary batteries by boron.

[0006] Therefore, an object of the present invention is to provide a method for producing a precursor of a positive electrode active material which does not require high-temperature heat treatment for introducing boron, and which, when used as a positive electrode active material, exhibits a high effect of increasing the capacity of a lithium-ion secondary battery and a high effect of suppressing gas generation during storage. [Means for solving the problem]

[0007] The method for producing a boron-containing transition metal carbonate disclosed herein includes the steps of preparing an initial aqueous solution containing an ammonium ion donor and a borate ion donor in a reaction vessel, and adding a raw material aqueous solution containing a transition metal, a boron source aqueous solution containing an ammonium donor and a borate ion donor, and a pH adjusting solution to the initial aqueous solution to form a reaction solution and perform a crystallization reaction. The pH of the initial aqueous solution at 25°C is in the range of 5.5 to 7.0. The oxygen concentration in the reaction vessel is 5% by volume or less. The transition metal includes at least Ni. The pH of the boron source aqueous solution at 25°C is in the range of 7.5 to 9.5. The pH adjusting solution includes a carbonate. The pH of the reaction solution at 25°C is in the range of 5.5 to 7.0.

[0008] According to this configuration, it is possible to provide a method for producing a precursor of a positive electrode active material which does not require high-temperature heat treatment for introducing boron, and which, when used as a positive electrode active material, exhibits a high effect of increasing the capacity of a lithium-ion secondary battery and a high effect of suppressing gas generation during storage. [Brief description of the drawings]

[0009] [Figure 1] 1 is a flowchart showing the steps of a method for producing a boron-containing transition metal carbonate according to one embodiment of the present invention. [Diagram 2] FIG. 1 is a cross-sectional view that illustrates a schematic internal structure of a lithium-ion secondary battery that uses a positive electrode active material obtained by a manufacturing method according to one embodiment of the present invention. [Diagram 3] 3 is a schematic exploded view showing the configuration of a wound electrode body of the lithium ion secondary battery of FIG. 2. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0010] Hereinafter, an embodiment of the present invention will be described with reference to the drawings. Matters not mentioned in this specification but necessary for carrying out the present invention can be understood as design matters for a person skilled in the art based on the prior art in the relevant field. The present invention can be carried out based on the contents disclosed in this specification and the technical common sense in the relevant field. In addition, in the following drawings, members and parts having the same function are described with the same reference numerals. Furthermore, the dimensional relationships (length, width, thickness, etc.) in each drawing do not reflect the actual dimensional relationships. In addition, the numerical range expressed as "A to B" in this specification includes A and B.

[0011] In this specification, the term "secondary battery" refers to an electricity storage device that can be repeatedly charged and discharged. In addition, in this specification, the term "lithium ion secondary battery" refers to a secondary battery that uses lithium ions as a charge carrier and realizes charging and discharging by the transfer of charge associated with the lithium ions between the positive and negative electrodes.

[0012] As shown in FIG. 1, the method for producing a boron-containing transition metal carbonate according to the present embodiment includes a step S101 of preparing an initial aqueous solution containing an ammonium ion donor and a borate ion donor in a reaction tank (hereinafter also referred to as an "initial aqueous solution preparation step"), and a step S102 of adding a raw material aqueous solution containing a transition metal, a boron source aqueous solution containing an ammonium donor and a borate ion donor, and a pH adjusting solution to the initial aqueous solution to form a reaction solution and perform a crystallization reaction (hereinafter also referred to as a "crystallization reaction step"). Here, the pH of the initial aqueous solution at 25°C is in the range of 5.5 to 7.0. The oxygen concentration in the reaction tank is 5% by volume or less. The transition metal contains at least Ni. The pH of the boron source aqueous solution at 25°C is in the range of 7.5 to 9.5. The pH adjusting solution contains a carbonate. The pH of the reaction solution at 25°C is in the range of 5.5 to 7.0.

[0013] First, the initial aqueous solution preparation step S101 will be described. A known reaction tank used in a crystallization reaction for synthesizing a precursor of a positive electrode active material can be used as the reaction tank. The reaction tank is a vessel for the crystallization reaction, and may be equipped with a stirrer such as a stirring blade, a thermometer, a pH meter, a gas introduction tube, a dropping funnel, and the like.

[0014] The type of ammonium donor is not particularly limited as long as it can supply ammonium ions. Examples of ammonium donors include ammonia, ammonium sulfate, ammonium chloride, ammonium carbonate, ammonium fluoride, etc. These can be used alone or in combination of two or more.

[0015] The type of borate ion donor is not particularly limited as long as it can supply borate ions. Examples of borate ion donors include boric acid, ammonium borate, boron oxide, etc. These can be used alone or in combination of two or more.

[0016] The ammonium donor and the borate ion donor may be used as they are in the preparation of the initial aqueous solution, or may be used in the form of an aqueous solution in the preparation of the initial reaction solution. The ammonium donor is preferably ammonia, and is preferably used in the form of aqueous ammonia.

[0017] The preparation of the initial aqueous solution can be carried out according to a known method. For example, the preparation can be carried out by supplying water to a reaction vessel, adding an ammonium donor and a borate ion donor thereto, and dissolving the ammonium donor and the borate ion donor in water. Alternatively, the preparation can be carried out by adding an aqueous solution of the ammonium donor and an aqueous solution of the borate ion donor to a reaction vessel to which water has been supplied or to which water has not been supplied.

[0018] The initial aqueous solution is prepared so that its pH at 25°C is 5.5 to 7.0. The pH can be adjusted by adjusting the amount of the ammonium donor and the borate ion donor. An acid (e.g., sulfuric acid, nitric acid, etc.) may be used to adjust the pH. The anion of the acid is preferably the same as the anion of the water-soluble salt of the transition metal described below. In this specification, the pH of the liquid at 25°C can be measured using a pH meter.

[0019] Here, a boron source aqueous solution containing an ammonium donor and a borate ion donor to be used in the next crystallization reaction step S102 may be prepared in advance and used to prepare the initial aqueous solution. In this case, the production method of this embodiment can be easily carried out. Here, the pH of the boron source aqueous solution at 25°C is 7.5 to 9.5. Therefore, for example, the boron source aqueous solution is supplied to a reaction tank to which water or no water has been supplied, and the pH of the initial aqueous solution is adjusted to be within the range of 5.5 to 7.0 using an acid.

[0020] Meanwhile, in the initial aqueous solution preparation step S101, the oxygen concentration in the reaction tank is adjusted to 5% by volume or less. The adjustment of the oxygen concentration can be performed according to a known method. For example, the oxygen concentration can be adjusted by introducing an inert gas such as nitrogen or argon into the reaction tank. The oxygen concentration in the reaction tank is preferably 4.5% by volume or less.

[0021] In this manner, the initial aqueous solution preparation step S101 can be carried out. Next, the crystallization reaction step S102 will be described.

[0022] The raw aqueous solution containing a transition metal to be used in the crystallization reaction step S102 can be prepared according to a known method, for example, by dissolving a water-soluble salt of the transition metal (e.g., a sulfate, a nitrate, a halide, etc. of the transition metal) in water.

[0023] Here, the boron-containing transition metal carbonate is a precursor of the lithium transition metal composite oxide (particularly, the lithium transition metal composite oxide having a layered structure) which is the positive electrode active material. Here, when the lithium transition metal composite oxide contains Ni, the effect of increasing the capacity of the lithium ion secondary battery and the effect of suppressing gas generation during storage are highly exhibited. Therefore, in this embodiment, the transition metal contains at least Ni.

[0024] The transition metal may also contain a transition metal other than Ni (particularly, a transition metal used in a lithium transition metal composite oxide known as a positive electrode active material). The lithium transition metal composite oxide is preferably a lithium nickel cobalt manganese composite oxide, since it can impart excellent properties to a lithium ion secondary battery. Therefore, the transition metal preferably contains at least Ni, Co, and Mn. In this case, the transition metal may further contain a transition metal element other than Ni, Co, and Mn.

[0025] Alternatively, the lithium transition metal composite oxide may be a lithium nickel cobalt aluminum composite oxide. Thus, the transition metal may contain at least Ni, Co, and Al. In this case, the transition metal may further contain transition metal elements other than Ni, Co, and Al.

[0026] When two or more kinds of transition metals are used, the raw material aqueous solutions may be prepared for each type of transition metal, or a single raw material aqueous solution containing two or more kinds of transition metals may be prepared.

[0027] The boron source aqueous solution containing an ammonium donor and a borate ion donor can be prepared by dissolving the above-mentioned ammonium donor and the above-mentioned borate ion donor in water so that the pH at 25°C is 7.5 to 9.5. One or both of the ammonium donor and the borate ion donor may be prepared in the form of an aqueous solution and mixed together. When the pH of the boron source aqueous solution at 25°C is within this range, the boron source can be sufficiently supplied to the reaction solution in the ion state (i.e., as borate ions). The pH of the boron source aqueous solution at 25°C is preferably 7.5 to 8.5, since this enhances the effect of increasing the capacity of the lithium ion secondary battery and the effect of suppressing gas generation during storage.

[0028] In addition, a pH adjusting solution containing a carbonate is used. By using a pH adjusting solution containing a carbonate, the precursor of the positive electrode active material can be precipitated as a carbonate. The pH adjusting solution is typically an aqueous solution of a carbonate. Examples of carbonates include sodium carbonate, sodium bicarbonate, potassium carbonate, and potassium bicarbonate. Among them, sodium carbonate is preferred.

[0029] A reaction solution is formed by adding a raw material aqueous solution containing a transition metal, a boron source aqueous solution, and a pH adjusting solution to an initial aqueous solution. At this time, the pH of the reaction solution at 25°C is controlled to the same range of 5.5 to 7.0 as the initial aqueous solution. By keeping the pH of the reaction solution within this range, boron can be efficiently introduced into the precipitated transition metal carbonate, and the effect of increasing the capacity of the lithium ion secondary battery and the effect of suppressing gas generation during storage can be highly exhibited. The pH of the reaction solution at 25°C is preferably 5.7 to 6.7. The pH of the reaction solution at 25°C can be adjusted by controlling the addition speed of the raw material aqueous solution containing a transition metal, the boron source aqueous solution, and the pH adjusting solution, etc.

[0030] In this case, when it is desired to introduce a metal other than a transition metal (e.g., an alkaline earth metal, etc.) into the boron-containing lithium transition metal composite oxide, an aqueous solution containing a metal other than a transition metal may be added. The metal other than a transition metal may be added to the raw aqueous solution containing the transition metal.

[0031] The temperature of the reaction solution is not particularly limited as long as the crystallization reaction can be carried out, and the reaction solution may or may not be heated. It is preferable that the reaction solution is not heated. The temperature of the reaction solution is, for example, higher than 0°C and not higher than 45°C, preferably 15°C to 40°C, and more preferably 25°C to 40°C.

[0032] The crystallization reaction time may be appropriately determined depending on the reaction scale, the desired particle size of the boron-containing transition metal carbonate, etc. The crystallization reaction time is, for example, 0.5 hours to 24 hours, and preferably 5 hours to 20 hours.

[0033] In the crystallization reaction step S102, the oxygen concentration in the reaction tank is also 5% by volume or less.

[0034] By performing the crystallization reaction in this way, a boron-containing transition metal carbonate can be precipitated. The precipitated boron-containing transition metal carbonate can be recovered according to a known method. For example, the precipitated boron-containing transition metal carbonate can be recovered by a solid-liquid separation method such as filtration, and washing and drying may be performed at this time.

[0035] The boron-containing transition metal carbonate is typically obtained in the form of secondary particles in which primary particles are aggregated. In the obtained boron-containing transition metal carbonate, boron exists not only on the surface of the secondary particles but also inside the secondary particles. Also, the amount of boron present can be higher inside the secondary particles than on the surface of the secondary particles.

[0036] The boron-containing transition metal carbonate preferably has a composition represented by the following formula (I). Ni (1-x-y-z-a) Co x Mn y B z A a CO3··· (I)

[0037] In the formula, x, y, z, and a each satisfy 0 ≦ x < 0.5, 0 ≦ y < 0.5, 0 < z < 0.1, and 0 ≦ a ≦ 0.05. A is at least one selected from the group consisting of Mg, Ca, V, Cr, Al, Ti, Zr, Nb, Mo, and W. x preferably satisfies 0.05 ≦ x ≦ 0.35, and y preferably satisfies 0.05 ≦ y ≦ 0.35.

[0038] Using the obtained boron-containing transition metal carbonate, a boron-containing lithium transition metal composite oxide can be produced according to a known method. By using the boron-containing lithium transition metal composite oxide as a positive electrode active material in a lithium ion secondary battery, the capacity of the lithium ion secondary battery can be increased and gas generation during storage can be suppressed.

[0039] From another aspect, the method for producing a positive electrode active material disclosed herein includes a step of synthesizing a boron-containing transition metal carbonate by the above-mentioned method (hereinafter also referred to as a "carbonate synthesis step"), a step of mixing the boron-containing transition metal carbonate with a lithium compound to obtain a raw material mixture (hereinafter also referred to as a "mixing step"), and a step of calcining the raw material mixture at 650°C to 1000°C for 3 hours to 8 hours (hereinafter also referred to as a "calcination step").

[0040] The carbonate synthesis step can be carried out by carrying out the method for producing a boron-containing transition metal carbonate according to the embodiment described above.

[0041] Here, before the mixing step, a step of heat-treating the boron-containing transition metal carbonate at 100° C. to 500° C. may be performed. The heat treatment can remove moisture contained in the boron-containing transition metal carbonate, thereby suppressing the occurrence of variation in the composition of the obtained positive electrode active material.

[0042] The lithium compound used in the mixing step is a Li source for the positive electrode active material. Examples of the lithium compound that can be used include compounds that are converted into oxides by firing, such as lithium carbonate, lithium nitrate, and lithium hydroxide.

[0043] The mixing ratio of the lithium source compound and the boron-containing transition metal carbonate may be appropriately determined according to the desired composition of the positive electrode active material. For example, in the positive electrode active material, the ratio of Li to metals other than Li is preferably 0.95 to 1.15. Therefore, it is preferable to mix so that the molar ratio of Li contained in the lithium source compound to the metal contained in the boron-containing transition metal carbonate is 0.95 to 1.15.

[0044] The mixing step can be carried out according to a known method, for example, by mixing the boron-containing transition metal carbonate and the lithium compound using a mixer such as a shaker mixer, a V blender, a ribbon mixer, a Julia mixer, or a Loedige mixer.

[0045] When it is desired to introduce a metal other than Li (also referred to as other metal) that is not contained in the boron-containing transition metal carbonate into the positive electrode active material, a source of the other metal may be mixed in the mixing step according to a known method.

[0046] The firing step can be carried out according to a known method. For example, the mixture can be fired using, for example, a batch-type electric furnace, a continuous-type electric furnace, or the like. The firing atmosphere is preferably an oxidizing atmosphere from the viewpoint of suppressing oxygen defects in the positive electrode active material. The oxidizing atmosphere is preferably an atmosphere with an oxygen concentration of 10% by volume or more, and may be an air atmosphere or an oxygen atmosphere (i.e., an atmosphere with an oxygen concentration higher than that of the air). The firing temperature is 650°C to 1000°C, preferably 700°C to 900°C. The firing time is 3 hours to 8 hours, preferably 3.5 hours to 7.5 hours.

[0047] In this manner, a boron-containing lithium transition metal composite oxide, which is a positive electrode active material, can be obtained. The boron-containing lithium transition metal composite oxide is typically obtained in the form of secondary particles formed by agglomeration of primary particles. In the obtained boron-containing lithium transition metal composite oxide, boron is present not only on the surface of the secondary particles but also inside the secondary particles. In addition, the amount of boron present inside the secondary particles may be higher than that on the surface of the secondary particles.

[0048] The positive electrode active material preferably has a composition represented by the following formula (II). Li d Ni (1-x-y-z-a) Co x Mn y B z A a O2··· (II)

[0049] In the formula, d, x, y, z, and a respectively satisfy 0.95 ≦ d ≦ 1.15, 0 ≦ x < 0.5, 0 ≦ y < 0.5, 0 < z < 0.1, and 0 ≦ a ≦ 0.05. A is at least one selected from the group consisting of Mg, Ca, V, Cr, Al, Ti, Zr, Nb, Mo, and W. x preferably satisfies 0.05 ≦ x ≦ 0.40, and y preferably satisfies 0.05 ≦ y ≦ 0.40.

[0050] The average particle diameter of the positive electrode active material is not particularly limited, but for example, it is 0.05 μm or more and 25 μm or less, preferably 1 μm or more and 20 μm or less, and more preferably 3 μm or more and 15 μm or less. Therefore, after the firing step, a step of adjusting the particle diameter of the boron-containing lithium transition metal composite oxide may be further performed. The adjustment of the particle diameter can be performed by a known method (e.g., crushing, classification, etc.). In this specification, the "average particle diameter" refers to the median diameter (D50). Therefore, in the volume-based particle size distribution based on the laser diffraction / scattering method, it means the particle diameter corresponding to 50 volume% of the cumulative frequency from the side of fine particles with a small particle diameter.

[0051] According to the positive electrode active material obtained by the above manufacturing method, a high capacity and high gas generation suppression performance during storage can be imparted to the lithium ion secondary battery. Therefore, the positive electrode active material obtained by the above manufacturing method is preferably the positive electrode active material of the lithium ion secondary battery. The lithium ion secondary battery can be configured according to a known method using the positive electrode active material obtained by the above manufacturing method.

[0052] Hereinafter, a configuration example of a lithium ion secondary battery using the positive electrode active material obtained by the above manufacturing method will be described with reference to FIGS. 2 and 3.

[0053] The lithium ion secondary battery 100 shown in FIG. 2 is a sealed battery constructed by housing a flat wound electrode body 20 and a nonaqueous electrolyte 80 in a flat rectangular battery case (i.e., an outer container) 30. The battery case 30 is provided with a positive electrode terminal 42 and a negative electrode terminal 44 for external connection, and a thin-walled safety valve 36 that is set to release the internal pressure when the internal pressure of the battery case 30 rises to a predetermined level or higher. The battery case 30 is also provided with an injection port (not shown) for injecting the nonaqueous electrolyte 80. The positive electrode terminal 42 is electrically connected to the positive electrode current collector plate 42a. The negative electrode terminal 44 is electrically connected to the negative electrode current collector plate 44a. The material of the battery case 30 is, for example, a lightweight metal material with good thermal conductivity, such as aluminum. Note that FIG. 2 does not accurately represent the amount of the nonaqueous electrolyte 80.

[0054] 2 and 3, the wound electrode body 20 has a configuration in which a positive electrode sheet 50 and a negative electrode sheet 60 are overlapped with two long separator sheets 70 interposed therebetween and wound in the longitudinal direction. The positive electrode sheet 50 has a configuration in which a positive electrode active material layer 54 is formed along the longitudinal direction on one or both sides (both sides here) of a long positive electrode current collector 52. The negative electrode sheet 60 has a configuration in which a negative electrode active material layer 64 is formed along the longitudinal direction on one or both sides (both sides here) of a long negative electrode current collector 62.

[0055] The positive electrode 50 has a positive electrode active material layer non-forming portion 52a where the positive electrode active material layer 54 is not formed and the positive electrode current collector 52 is exposed. The negative electrode 60 has a negative electrode active material layer non-forming portion 62a where the negative electrode active material layer 64 is not formed and the negative electrode current collector 62 is exposed. The positive electrode active material layer non-forming portion 52a and the negative electrode active material layer non-forming portion 62a are formed so as to protrude outward from both ends in the winding axis direction (i.e., the sheet width direction perpendicular to the longitudinal direction) of the wound electrode body 20. The positive electrode active material layer non-forming portion 52a and the negative electrode active material layer non-forming portion 62a are joined to the positive electrode current collector 42a and the negative electrode current collector 44a, respectively.

[0056] A known positive electrode current collector used in lithium ion secondary batteries may be used as the positive electrode current collector 52, and examples thereof include a sheet or foil made of a metal having good electrical conductivity (e.g., aluminum, nickel, titanium, stainless steel, etc.). As the positive electrode current collector 52, aluminum foil is preferred.

[0057] The dimensions of the positive electrode current collector 52 are not particularly limited and may be appropriately determined depending on the battery design. When an aluminum foil is used as the positive electrode current collector 52, the thickness is not particularly limited, but is, for example, 5 μm or more and 35 μm or less, and preferably 7 μm or more and 20 μm or less.

[0058] The positive electrode active material layer 54 contains a positive electrode active material. The positive electrode active material is obtained by the manufacturing method according to the above-mentioned embodiment. The positive electrode active material layer 54 may contain other positive electrode active materials in addition to the positive electrode active material obtained by the manufacturing method according to the above-mentioned embodiment, within a range that does not impair the effects of the present invention.

[0059] The positive electrode active material layer 54 may contain components other than the positive electrode active material, such as trilithium phosphate, a conductive material, a binder, etc. As the conductive material, for example, carbon black such as acetylene black (AB) or other carbon materials (e.g., graphite, carbon nanotubes, etc.) can be suitably used. As the binder, for example, polyvinylidene fluoride (PVDF) can be used.

[0060] The content of the positive electrode active material in the positive electrode active material layer 54 (i.e., the content of the positive electrode active material relative to the total mass of the positive electrode active material layer 54) is not particularly limited, but is preferably 70 mass% or more, more preferably 80 mass% to 99 mass% or less, and even more preferably 85 mass% to 98 mass% or less. The content of the conductive material in the positive electrode active material layer 54 is not particularly limited, but is preferably 0.5 mass% to 15 mass% or less, and more preferably 1 mass% to 10 mass% or less. The content of the binder in the positive electrode active material layer 54 is not particularly limited, but is preferably 0.5 mass% to 15 mass% or less, and more preferably 0.8 mass% to 10 mass% or less.

[0061] The thickness of the positive electrode active material layer 54 is not particularly limited, but is, for example, from 10 μm to 300 μm, and preferably from 20 μm to 200 μm.

[0062] In the positive electrode sheet 50, the positive electrode active material layer non-forming portion 52a may be provided with an insulating protective layer (not shown) containing insulating particles at a position adjacent to the positive electrode active material layer 54. This protective layer can prevent a short circuit between the positive electrode active material layer non-forming portion 52a and the negative electrode active material layer 64.

[0063] A known negative electrode current collector used in lithium ion secondary batteries may be used as the negative electrode current collector 62, and examples thereof include a sheet or foil made of a metal having good electrical conductivity (e.g., copper, nickel, titanium, stainless steel, etc.). Copper foil is preferable as the negative electrode current collector 62.

[0064] The dimensions of the negative electrode current collector 62 are not particularly limited and may be appropriately determined depending on the battery design. When a copper foil is used as the negative electrode current collector 62, the thickness is not particularly limited, but is, for example, 5 μm or more and 35 μm or less, and preferably 7 μm or more and 20 μm or less.

[0065] The negative electrode active material layer 64 contains a negative electrode active material. As the negative electrode active material, for example, a carbon material such as graphite, hard carbon, soft carbon, etc. The graphite may be natural graphite or artificial graphite, or may be amorphous carbon-coated graphite in which graphite is coated with an amorphous carbon material.

[0066] The average particle diameter (median diameter: D50) of the negative electrode active material is not particularly limited, but is, for example, 0.1 μm to 50 μm, preferably 1 μm to 25 μm, and more preferably 5 μm to 20 μm. The average particle diameter (D50) of the negative electrode active material can be determined, for example, by a laser diffraction scattering method.

[0067] The negative electrode active material layer 64 may contain components other than the active material, such as a binder, a thickener, etc. As the binder, for example, styrene butadiene rubber (SBR), polyvinylidene fluoride (PVDF), etc. may be used. As the thickener, for example, carboxymethyl cellulose (CMC), etc. may be used.

[0068] The content of the negative electrode active material in the negative electrode active material layer 64 is preferably 90% by mass or more, and more preferably 95% by mass or more and 99% by mass or less. The content of the binder in the negative electrode active material layer 64 is preferably 0.1% by mass or more and 8% by mass or less, and more preferably 0.5% by mass or more and 3% by mass or less. The content of the thickener in the negative electrode active material layer 64 is preferably 0.3% by mass or more and 3% by mass or less, and more preferably 0.5% by mass or more and 2% by mass or less.

[0069] The thickness of the negative electrode active material layer 64 is not particularly limited, but is, for example, not less than 10 μm and not more than 300 μm, and preferably not less than 20 μm and not more than 200 μm.

[0070] The separator 70 may be a porous sheet (film) made of a resin such as polyethylene (PE), polypropylene (PP), polyester, cellulose, or polyamide. Such a porous sheet may have a single-layer structure or a laminated structure of two or more layers (for example, a three-layer structure in which a PP layer is laminated on both sides of a PE layer). A heat-resistant layer (HRL) may be provided on the surface of the separator 70.

[0071] The thickness of the separator 70 is not particularly limited, but is, for example, from 5 μm to 50 μm, and preferably from 10 μm to 30 μm.

[0072] The nonaqueous electrolyte 80 typically contains a nonaqueous solvent and a supporting salt (electrolyte salt). As the nonaqueous solvent, various organic solvents such as carbonates, ethers, esters, nitriles, sulfones, and lactones that are used in electrolytes of general lithium ion secondary batteries can be used without any particular limitation. Specific examples include ethylene carbonate (EC), propylene carbonate (PC), diethyl carbonate (DEC), dimethyl carbonate (DMC), ethyl methyl carbonate (EMC), monofluoroethylene carbonate (MFEC), difluoroethylene carbonate (DFEC), monofluoromethyl difluoromethyl carbonate (F-DMC), and trifluorodimethyl carbonate (TFDMC). Such nonaqueous solvents can be used alone or in appropriate combination of two or more.

[0073] As the supporting salt, for example, a lithium salt such as LiPF6, LiBF4, lithium bis(fluorosulfonyl)imide (LiFSI) (preferably LiPF6) can be suitably used. The concentration of the supporting salt is preferably 0.7 mol / L or more and 1.3 mol / L or less.

[0074] The nonaqueous electrolyte 80 may contain various additives other than the above-mentioned components, such as film-forming agents such as vinylene carbonate (VC) and oxalate complexes; gas generating agents such as biphenyl (BP) and cyclohexylbenzene (CHB); and thickeners, as long as the effects of the present invention are not significantly impaired.

[0075] The lithium ion secondary battery 100 configured as described above has a high capacity and suppresses gas generation during storage. The lithium ion secondary battery 100 can be used for various purposes. Specific applications include portable power sources for personal computers, portable electronic devices, portable terminals, etc.; power sources for driving vehicles such as electric vehicles (BEVs), hybrid vehicles (HEVs), plug-in hybrid vehicles (PHEVs), etc.; and storage batteries for small power storage devices, among which a power source for driving vehicles is preferable. The lithium ion secondary battery 100 can also be used in the form of a battery pack in which a plurality of batteries are typically connected in series and / or in parallel.

[0076] As an example, a rectangular lithium ion secondary battery 100 including a flat wound electrode assembly 20 has been described. However, the nonaqueous electrolyte secondary battery disclosed herein can also be configured as a lithium ion secondary battery including a laminated electrode assembly (i.e., an electrode assembly in which multiple positive electrodes and multiple negative electrodes are alternately laminated). The laminated electrode assembly may include multiple separators such that one separator is interposed between each of the positive and negative electrodes, and may be one in which positive electrodes and negative electrodes are alternately laminated with one separator folded back.

[0077] The lithium ion secondary battery 100 can also be configured as a coin type lithium ion secondary battery, a button type lithium ion secondary battery, a cylindrical lithium ion secondary battery, or a laminate case type lithium ion secondary battery.

[0078] On the other hand, an all-solid-state lithium ion secondary battery can be constructed using the positive electrode active material obtained by the manufacturing method according to this embodiment and a solid electrolyte instead of the nonaqueous electrolyte 80 according to a known method.

[0079] Examples of the present invention will be described below, but it is not intended that the present invention be limited to those shown in these examples. In the following description, "pH" is a value at a liquid temperature of 25°C.

[0080] Example 1 <Preparation of boron-containing transition metal carbonates> As an ammonium donor, ammonia water with a concentration of 1% by mass was prepared. As a borate ion donor, a boric acid aqueous solution with a concentration of 0.3 mol% was prepared. This ammonia water and the boric acid aqueous solution were mixed so that the pH was 8.2 to prepare a boron source aqueous solution.

[0081] The boron source aqueous solution was fed into a 5 L reaction vessel and stirred at 600 rpm. Nitrogen was also introduced into the reaction vessel to adjust the oxygen concentration in the reaction vessel to 3% by volume. The pH of the boron source aqueous solution was then adjusted to 6.5 using sulfuric acid with a concentration of 1 mol%, to obtain an initial aqueous solution.

[0082] Nickel sulfate, cobalt sulfate, and manganese sulfate were dissolved in water in a molar ratio of 1:1:1 to prepare a raw metal aqueous solution with a concentration of 1 mol / L. A sodium carbonate aqueous solution with a concentration of 0.5 mol / L was prepared as a pH adjusting solution.

[0083] The raw metal aqueous solution prepared above, the pH adjusting solution, and the boron source aqueous solution were supplied to the reaction tank at a volume ratio of 1:1:1, and the crystallization reaction was carried out for 10 hours under the condition of pH 6.5. The obtained product was washed with water, filtered, and dried to obtain a powdered boron-containing transition metal carbonate (i.e., boron-containing nickel-cobalt-manganese composite carbonate).

[0084] <Preparation of positive electrode active material> The boron-containing nickel-cobalt-manganese composite carbonate prepared above was mixed with a lithium compound such that the total moles of nickel, cobalt, and manganese and the moles of lithium were 1:1.1. The resulting mixture was fired in a firing furnace at 780°C in an oxidizing atmosphere for 6 hours. This produced a boron-containing lithium-nickel-cobalt-manganese composite oxide, which is a positive electrode active material.

[0085] Example 2 An initial aqueous solution was obtained in the same manner as in Example 1, except that the stirring speed was changed to 700 rpm and the pH of the boron source aqueous solution was changed to a value shown in Table 2. A crystallization reaction was carried out in the same manner as in Example 1, except that the obtained initial aqueous solution was used, to obtain a powdered boron-containing transition metal carbonate.

[0086] Using the obtained boron-containing transition metal carbonate, a boron-containing lithium nickel cobalt manganese composite oxide, which is a positive electrode active material, was obtained in the same manner as in Example 1, except that the firing temperature and firing time were changed to those shown in Table 2.

[0087] Example 3 An initial aqueous solution was obtained in the same manner as in Example 1, except that the stirring speed was changed to 700 rpm, and the pH of the boron source aqueous solution, the oxygen concentration in the reaction layer, and the pH of the initial aqueous solution were changed to the values ​​shown in Table 2. Using the obtained initial aqueous solution, a crystallization reaction was carried out in the same manner as in Example 1, except that the pH of the reaction solution during the crystallization reaction was changed to the value shown in Table 2, and the reaction time was changed to 11 hours, to obtain a powdered boron-containing transition metal carbonate.

[0088] The boron-containing nickel-cobalt-manganese composite carbonate prepared above and a lithium compound were mixed such that the total moles of nickel, cobalt, and manganese and the moles of lithium were 1:1.2. Except for changing the firing temperature and firing time to those shown in Table 2, firing was performed in the same manner as in Example 1 to obtain a boron-containing lithium-nickel-cobalt-manganese composite oxide as a positive electrode active material.

[0089] Example 4 An initial aqueous solution was obtained in the same manner as in Example 1, except that the stirring speed was changed to 700 rpm and the pH of the aqueous boron source solution was changed to a value shown in Table 2.

[0090] Nickel sulfate, cobalt sulfate, manganese sulfate, and zirconium sulfate were dissolved in water in a molar ratio of 55.9:19.9:19.9:0.3 to prepare a raw metal aqueous solution with a concentration of 1 mol / L. A crystallization reaction was carried out in the same manner as in Example 1, except that this raw metal aqueous solution and the obtained initial aqueous solution were used, to obtain a powdered boron-containing transition metal carbonate.

[0091] Using the obtained boron-containing transition metal carbonate, a boron-containing lithium nickel cobalt manganese composite oxide, which is a positive electrode active material, was obtained in the same manner as in Example 1, except that the firing temperature and time were changed to those shown in Table 2.

[0092] Comparative Example 1 An initial aqueous solution was obtained in the same manner as in Example 1, except that the stirring speed was changed to 700 rpm, and the pH of the boron source aqueous solution, the oxygen concentration in the reaction layer, and the pH of the initial aqueous solution were changed to the values ​​shown in Table 2. Using the obtained initial aqueous solution, a crystallization reaction was carried out in the same manner as in Example 1, except that the pH of the reaction solution during the crystallization reaction was changed to the value shown in Table 2, and the reaction time was changed to 11 hours, to obtain a powdered boron-containing transition metal carbonate.

[0093] A boron-containing lithium nickel cobalt manganese composite oxide, which is a positive electrode active material, was obtained in the same manner as in Example 1, except that the obtained boron-containing transition metal carbonate was used.

[0094] [Comparative Examples 2 to 5] An initial aqueous solution was obtained in the same manner as in Example 1, except that the stirring speed was changed to 700 rpm, and the pH of the boron source aqueous solution, the oxygen concentration in the reaction layer, and the pH of the initial aqueous solution were set to the values ​​shown in Table 2. Using the obtained initial aqueous solution, a crystallization reaction was carried out in the same manner as in Example 1, except that the pH of the reaction liquid during the crystallization reaction was set to the value shown in Table 2, to obtain a powdered boron-containing transition metal carbonate.

[0095] Using the obtained boron-containing transition metal carbonate, a boron-containing lithium nickel cobalt manganese composite oxide, which is a positive electrode active material, was obtained in the same manner as in Example 1, except that the firing temperature and firing time were set to the temperatures and times shown in Table 2.

[0096] <ICP analysis of boron-containing transition metal carbonates> The compositions of the boron-containing transition metal carbonates obtained in Examples 1 to 4 and Comparative Example 1 were analyzed using a commercially available ICP emission spectrometer. As a result, the atomic ratios of Ni, Co, Mn, and B were as shown in the following Table 1. In Example 4, the atomic ratio of Zr was also determined.

[0097] [Table 1]

[0098] <Preparation of lithium-ion secondary battery for evaluation> The positive electrode active material prepared above, acetylene black (AB) as a conductive material, and polyvinylidene fluoride (PVdF) as a binder were mixed with N-methylpyrrolidone (NMP) in a mass ratio of active material:AB:PVdF=100:1:1 to prepare a positive electrode slurry. This positive electrode slurry was applied to both sides of an aluminum foil having a thickness of 15 μm. At this time, a positive electrode slurry uncoated portion was provided on the aluminum foil as a lead connection portion. The applied slurry was dried to form a positive electrode active material layer. After the positive electrode active material layer was roll-pressed, the obtained sheet was processed to a predetermined size to obtain a positive electrode sheet.

[0099] Graphite (C) as a negative electrode active material, carboxymethyl cellulose (CMC), and styrene butadiene rubber (SBR) were mixed with water in a mass ratio of C:CMC:SBR=98:1:1 to prepare a negative electrode slurry. This negative electrode slurry was applied to both sides of a copper foil. At this time, a negative electrode slurry uncoated portion was provided on the copper foil as a lead connection portion. The applied slurry was dried to form a negative electrode active material layer. After the negative electrode active material layer was roll-pressed, the obtained sheet was processed to a predetermined size to obtain a negative electrode sheet.

[0100] A lead was attached to each of the positive and negative electrodes prepared as above. A single-layer polypropylene separator was prepared. The positive and negative electrodes were laminated with the separator interposed therebetween to prepare an electrode assembly.

[0101] A mixed solvent containing ethylene carbonate (EC), dimethyl carbonate (DMC), and ethyl methyl carbonate (EMC) in a volume ratio of 30:40:30 was prepared. Vinylene carbonate was dissolved in this mixed solvent at a concentration of 2 mass%, lithium bis(oxalate)borate was dissolved in a concentration of 0.8 mass%, and LiPF6 was dissolved as a supporting salt at a concentration of 1.15 mol / L. This resulted in a nonaqueous electrolyte.

[0102] The electrode body and the non-aqueous electrolyte solution prepared above were housed in a battery case made of a laminate film and sealed to obtain a lithium ion secondary battery for evaluation.

[0103] <Discharge capacity evaluation> Each of the lithium ion secondary batteries for evaluation prepared above was placed in an environment of 25°C. Each of the lithium ion secondary batteries for evaluation was charged at a constant current of 1 / 3C to 4.2V, and then charged at a constant voltage until the current value reached 0.01C. Next, each of the lithium ion secondary batteries for evaluation was discharged at a constant current of 1 / 3C to 3.0V. The discharge capacity at this time was measured. The results are shown in Table 2.

[0104] <Gas generation rate evaluation> The volume of each evaluation lithium ion secondary battery was determined by the Archimedes method using Fluorinert as a solvent. This volume was defined as the initial volume. Next, in an environment of 25°C, each evaluation lithium ion secondary battery was charged at a constant current of 0.3C up to 4.4V, and then charged at a constant voltage until the current value reached 0.01C. Each charged evaluation lithium ion secondary battery was placed in a thermostatic chamber at 60°C and stored for 24 hours. Then, each evaluation lithium ion secondary battery was allowed to cool in an environment of 25°C. Again, the volume of each evaluation lithium ion secondary battery was determined by the Archimedes method using Fluorinert as a solvent. The difference (mL) between the volume after storage and the initial volume was determined and defined as the amount of gas generated. The results are shown in Table 2.

[0105] [Table 2]

[0106] The results in Table 1 show that, regarding the conditions for producing a transition metal carbonate containing nickel and boron, when the pH of the initial aqueous solution is in the range of 5.5 to 7.0, the pH of the boron source aqueous solution is in the range of 7.5 to 9.5, the pH of the reaction solution is in the range of 5.5 to 7.0, and the oxygen concentration in the reaction tank is 5% by volume or less, the amount of gas generated during storage is small and at the same time the discharge capacity is high. Therefore, it is found that boron can be efficiently introduced into the transition metal carbonate, which is the precursor of the positive electrode active material, without performing a high-temperature heat treatment for boron.

[0107] It is also found that the preferred firing conditions for converting the transition metal carbonate into a positive electrode active material are a firing temperature in the range of 650° C. to 1000° C. and a firing time in the range of 3 hours to 8 hours.

[0108] Therefore, from the above results, it is evident that the method for producing a boron-containing transition metal carbonate disclosed herein does not require high-temperature heat treatment for introducing boron, and makes it possible to produce a precursor of a positive electrode active material that, when used as a positive electrode active material, highly exhibits the effect of increasing the capacity of a lithium-ion secondary battery and the effect of suppressing gas generation during storage.

[0109] Although the specific examples of the present invention have been described in detail above, these are merely examples and do not limit the scope of the claims. The technology described in the claims includes various modifications and changes of the specific examples exemplified above.

[0110] That is, the method for producing a boron-containing transition metal carbonate and the method for producing a positive electrode active material disclosed herein include the following items [1] to [4]. [1] preparing an initial aqueous solution containing an ammonium ion donor and a borate ion donor in a reaction vessel; and A step of adding a raw material aqueous solution containing a transition metal, a boron source aqueous solution containing an ammonium donor and a borate ion donor, and a pH adjusting solution to the initial aqueous solution to form a reaction solution and perform a crystallization reaction. Equipped with The pH of the initial aqueous solution at 25° C. is within the range of 5.5 to 7.0; The oxygen concentration in the reaction tank is 5% by volume or less, The transition metal includes at least Ni, The pH of the boron source aqueous solution at 25°C is within the range of 7.5 to 9.5; The pH adjusting solution contains a carbonate, The pH of the reaction solution at 25°C is within the range of 5.5 to 7.0. A method for producing a boron-containing transition metal carbonate. [2] The method for producing a boron-containing transition metal carbonate according to item [1], wherein the transition metal contains at least Ni, Co, and Mn. [3] The method for producing a boron-containing transition metal carbonate according to item [1] or [2], wherein the pH of the aqueous boron source solution at 25° C. is within the range of 7.5 to 8.5. [4] A step of synthesizing a boron-containing transition metal carbonate by the method according to any one of items [1] to [3]; mixing the boron-containing transition metal carbonate with a lithium compound to obtain a raw material mixture; and A step of firing the raw material mixture at 650°C to 1000°C for 3 hours to 8 hours. The method for producing a positive electrode active material includes the steps of: [Explanation of symbols]

[0111] 20 Wound electrode body 30 Battery case 36 Safety valve 42 Positive terminal 42a Positive current collector 44 Negative terminal 44a Negative current collector plate 50 Positive electrode sheet (positive electrode) 52 Positive electrode current collector 52a Exposed part of positive electrode current collector 54 Cathode active material layer 60 Negative electrode sheet (negative electrode) 62 Negative electrode current collector 62a Exposed part of negative electrode current collector 64 Negative electrode active material layer 70 Separator sheet (separator) 80 Non-aqueous electrolytes 100 Lithium-ion secondary battery

Claims

1. preparing an initial aqueous solution containing an ammonium ion donor and a borate ion donor in a reaction vessel; A step of adding a raw material aqueous solution containing a transition metal, a boron source aqueous solution containing an ammonium donor and a borate ion donor, and a pH adjusting solution to the initial aqueous solution to form a reaction solution and perform a crystallization reaction. Equipped with The pH of the initial aqueous solution at 25° C. is in the range of 5.5 to 7.0; The oxygen concentration in the reaction tank is 5% by volume or less, The transition metal includes at least Ni, The pH of the aqueous boron source solution at 25° C. is within the range of 7.5 to 9.5; The pH adjusting solution contains a carbonate, The pH of the reaction solution at 25°C is within the range of 5.5 to 7.

0. A method for producing a boron-containing transition metal carbonate.

2. The method for producing a boron-containing transition metal carbonate according to claim 1 , wherein the transition metal contains at least Ni, Co, and Mn.

3. 2. The method for producing a boron-containing transition metal carbonate according to claim 1, wherein the pH of the aqueous boron source solution at 25° C. is in the range of 7.5 to 8.

5.

4. 2. Synthesizing a boron-containing transition metal carbonate by the method of claim 1; mixing the boron-containing transition metal carbonate with a lithium compound to obtain a raw material mixture; and A step of firing the raw material mixture at 650° C. to 1000° C. for 3 hours to 8 hours. The method for producing a positive electrode active material includes the steps of:

Citation Information

Patent Citations

  • Positive electrode active material, production method therefor, positive electrode composite material using positive electrode active material, positive electrode for nonaqueous electrolyte secondary battery and nonaqueous electrolyte secondary battery

    JP2016201209A

  • Positive electrode active material for nonaqueous electrolyte secondary battery, method for manufacturing the same, positive electrode for nonaqueous electrolyte secondary battery, and nonaqueous electrolyte secondary battery

    JP2018073481A

  • Positive electrode active material precursor for nonaqueous electrolyte secondary battery, positive electrode active material for nonaqueous electrolyte secondary battery, method for manufacturing positive electrode active material precursor for nonaqueous electrolyte secondary battery, and method for manufacturing positive electrode active material for nonaqueous electrolyte secondary battery

    JP2019003818A

  • Positive electrode active material for lithium secondary battery and method for producing same

    JP2022507671A

  • Manufacturing method of positive active material

    JP2009146739A